Pengaruh Lingkungan Kerja dan Kompensasi Terhadap Kinerja Melalui Motivasi Karyawan Bagian Produksi UD.Lumintu Ambulu Jember - Elok Faiqotul Jannah; Diana Sulianti K. Tobing; Sunardi Sunardi (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
This research aims to know and analyze the influence of the work environment and compensation on performance throughmotivation of the production employees UD.Lumintu Ambulu Jember. This research perform with explanatory research. Thesample was 35 respondents. The population in this study as well as samples so this research included in the populationresearch (census). These results indicate that the work environment and compensation effect directly or indirectly to theperformance through motivation of the production employees UD.Lumintu Ambulu Jember.